Mathematical Problem-Solving Ability of Junior High School Students in Terms of Self-Directed Learning - Divia Raina Rami; Amma Achiaa (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2025)
Self-directed learning (SDL) is a crucial factor that can significantly improve students’ math problem-solving abilities (MPSA), particularly in 21st-century education, which emphasizes independence and critical thinking. This study aims to compare the math problem-solving abilities of junior high school students based on their self-directed learning categories. The research used a mixed-methods approach with a sequential explanatory design. It began with a quantitative phase, analyzing 82 eighth-grade students from one of the public junior high schools in West Bandung Regency through a problem-solving test and an SDL questionnaire. This was followed by a qualitative phase involving semi-structured interviews with three selected participants. The statistical results from the Welch test and Games-Howell post hoc analysis showed significant differences in math problem-solving abilities among students with high, moderate, and low SDL categories. The qualitative findings supported these results, indicating that students with high SDL were better at understanding problems, developing strategies, and reflecting independently on solutions. In contrast, students with low SDL displayed limitations in these areas. This study highlights the importance of adopting learning approaches that foster SDL in math education to enhance students’ problem-solving skills comprehensively. It also provides a theoretical contribution toward developing more adaptive, student-centered math learning strategies tailored to individual needs in 21st-century education.